2011
DOI: 10.1002/9780470559277.ch110180
|View full text |Cite
|
Sign up to set email alerts
|

Target Identification Using Drug Affinity Responsive Target Stability (DARTS)

Abstract: Drug affinity responsive target stability (DARTS) is a general methodology for identifying and studying protein‐ligand interactions. The technique is based on the principle that when a small molecule compound binds to a protein, the interaction stabilizes the target protein's structure such that it becomes resistant to proteases. DARTS is particularly useful for the initial identification of the protein targets of small molecules, but can also be used to validate potential protein‐ligand interactions predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
230
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(241 citation statements)
references
References 14 publications
4
230
0
Order By: Relevance
“…The Drug Affinity Responsive Target Stability (DARTS) assay was optimized and used to assess the binding of SC144 on MDA-7/IL-24 via the protease protection from pronase (Roche Applied Science, Inc.) as previously described [43,44]. HCT116 p53+/+ cells were lysed using M-PER (Thermo Scientific, Inc.) supplemented with protease inhibitors and phosphatase inhibitors.…”
Section: Darts Assaymentioning
confidence: 99%
“…The Drug Affinity Responsive Target Stability (DARTS) assay was optimized and used to assess the binding of SC144 on MDA-7/IL-24 via the protease protection from pronase (Roche Applied Science, Inc.) as previously described [43,44]. HCT116 p53+/+ cells were lysed using M-PER (Thermo Scientific, Inc.) supplemented with protease inhibitors and phosphatase inhibitors.…”
Section: Darts Assaymentioning
confidence: 99%
“…Huang and coworkers developed a label-free method named drug affinity responsive target stability (DARTS, Fig. 2c), (Pai et al 2015) which utilizes the higher resistance of proteins to proteolysis after ligand binding (Lomenick et al 2009(Lomenick et al , 2011a. In a recent example, DARTS successfully identified the target of a-ketoglutarate, a tricarboxylic acid cycle intermediate which can extend the lifespan of adult Caenorhabditis elegans; this study revealed new roles of a common metabolite in the regulation of organismal lifespan (Chin et al 2014).…”
Section: Probe Modification and Label-free Probes In Affinity Purificmentioning
confidence: 94%
“…The ratio of peak intensities in the mass spectrum reflects the abundance ratio for the proteins. Another technique called drug affinity responsive target stability (DARTS) is based on the principle that drug-target binding can form a more stable complex relative to a bare protein (Lomenick et al, 2009). Briefly, cell lysate is incubated with drug molecules and vehicles, and the subsequent proteolysis process will degrade most proteins except the chemical-linked complex, which is then visualized on gel bands.…”
Section: The Concept Of the Chemical-protein Interactomementioning
confidence: 99%